Therapeutic potential of oxazole scaffold: a patent review (2006–2017). (2nd November 2018) - Kaur, Ramandeep; Palta, Kezia; Kumar, Manoj; Bhargava, Meha; Dahiya, Lalita
ABSTRACT: Introduction : Oxazoles are oxygen and nitrogen containing five membered heterocyclic ring systems that are present in various anticancer, antimicrobial, antihyperglycemic, anti-inflammatory agents etc . of natural origin. These pharmacologically active oxazole derivatives have attracted numerous researchers to explore this scaffold for the design and development of newer potential therapeutic agents. A large number of synthetic oxazole containing molecules have been reported over the period that exhibited wide spectrum of pharmacological profiles. Some of them have shown promising therapeutic potential and have qualified for both preclinical and clinical evaluations. Areas covered : In this review, the patents (published during 2006–2017) focusing on the biological potential of oxazoles have been covered. Therapeutic applications and various techniques/assays employed for the in vitro/in vivo evaluation of patented derivatives have been discussed majorly. Expert opinion : Chemically oxazole offers three positions for substitution. These substituted oxazole derivatives of natural as well as synthetic origin have numerous pharmacological applications including anticancer, anti-Alzheimer's, anti-hyperglycemic, anti-inflammatory, antibacterial etc . Their pharmacological actions are mainly mediated through enzyme/receptor involved in the particular disease. The flexible nature of this ligand for various molecular level targets (enzyme/receptor) make this heterocylce an attractive scaffold for development of effective and clinically relevant oxazole containing therapeutic agents.